Combining ability analysis for yield and its component traits in groundnut (Arachis hypogaea L.) - R. Prabhu1*, N. Manivannan1, A. Mothilal2 and S.M. Ibrahim3 (Electronic Journal of Plant Breeding, 2014)
Line × tester analysis was carried out involving six lines and three testers in groundnut for assessing the combining ability for yield and its component characters. Hybrids recorded significant variance for all characters studied. Variance due to parents showed significance for all characters except for shell weight, pod yield per plant, kernel yield per plant and oil yield per plant. The variance due to hybrids vs parents had significance for all characters except for plant height, shelling percentage, oil content and rust disease scores. In case of combining ability ANOVA, lines showed significant variance for all characters except for sound mature kernel. Significant differences were present among the testers for characters viz., plant height and number of pods per plant. The variance due to line x tester had significance for all characters except for 100-kernel weight, oil content, late leaf spot and rust disease scores. The SCA variances were higher than GCA variances indicating the predominance of non-additive gene action for all the characters studied. The parent ICGV 03128 proved to be a good general combiner for oil yield and other economic traits and hence need to be included in the oil yield improvement programmes. The hybrid combinations viz., ICGV 00350 × VRI Gn 6, CO 7 × GPBD 4, ICGV 03128 × GPBD 4, ICGV 03128 × COG 0437 and ICGV 03128 × VRI Gn 6 recorded superior per se for oil yield per plant. Among these crosses ICGV 03128 × GPBD 4 and ICGV 03128 × VRI Gn 6 exhibited additive type gene action with one good general combining ability parent for oil yield per plant, oil content, kernel yield per plant and other characters. Hence, selection can be made in these crosses in early generation itself. The disease scores viz., late leaf spot and rust also recorded non significant sca values indicating that these traits are controlled by additive gene action.